2014
DOI: 10.3389/fmicb.2014.00068
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Listeria monocytogenes exposed to biocide stress reveals a multi-system response involving cell wall synthesis, sugar uptake, and motility

Abstract: Listeria monocytogenes is a virulent food-borne pathogen most often associated with the consumption of “ready-to-eat” foods. The organism is a common contaminant of food processing plants where it may persist for extended periods of time. A commonly used approach for the control of Listeria monocytogenes in the processing environment is the application of biocides such as quaternary ammonium compounds. In this study, the transcriptomic response of a persistent strain of L. monocytogenes (strain 6179) on exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Presence of the gene pair ykkCD was shown to increase tolerance to, for example, EtBr, CPC, crystal violet and tetracycline in E. coli (Jack et al ., ). Increased expression of qacH , ykkC , lmrB , ykkD and other transporters as well as many genes involved in various biological functions has recently been reported when L. monocytogenes 6179 was exposed to sublethal concentrations of BZT (Casey et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of the gene pair ykkCD was shown to increase tolerance to, for example, EtBr, CPC, crystal violet and tetracycline in E. coli (Jack et al ., ). Increased expression of qacH , ykkC , lmrB , ykkD and other transporters as well as many genes involved in various biological functions has recently been reported when L. monocytogenes 6179 was exposed to sublethal concentrations of BZT (Casey et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Usage of more than one reference gene will improve reliability; nevertheless, the 16S rRNA gene was the most stably expressed housekeeping gene in L. monocytogenes in a study conducted by Tasara and Stephan (Tasara & Stephan, ). Furthermore, our results are confirmed by a recent study using RNAseq of L. monocytogenes 6179 (harbouring a Tn 6188 copy, which is identical to Tn 6188 from strain 4423), which showed a fourfold upregulation of qacH in the presence of BZT (Casey et al ., ) – similar to what we observe here. Although qRT‐PCR supports our MIC data that QacH's substrate spectrum comprises various QACs, indirect effects during deletion and complementation may influence MICs.…”
Section: Resultsmentioning
confidence: 99%
“…It possesses a 3.01 Mbp genome and a 62.2 kbp plasmid, designated pLM6179 (Schmitz-Esser et al, 2015b). Notably, the stress survival characteristics of L. monocytogenes 6179 have been extensively characterized (Müller et al, 2013(Müller et al, , 2014Casey et al, 2014;Makariti et al, 2015;Rychli et al, 2016;Harter et al, 2017;Naditz et al, 2019). L. monocytogenes strain R479a is an ST8 strain isolated from smoked salmon in Denmark in 1996 where it persisted for more than 2 years in the same FPE (Fonnesbech Vogel et al, 2001;Schmitz-Esser et al, 2015a).…”
Section: Bacterial Strains Used In This Studymentioning
confidence: 99%
“…Upon exposure to environmental stress conditions found in food and FPEs, L. monocytogenes responds by activating a wide variety of mechanisms that confer stress tolerance (Dutta et al, 2013;Müller et al, 2013;Harter et al, 2017;Bucur et al, 2018;Hingston et al, 2019). In addition to functional characterization, multiple gene expression analyses have implicated many genes in the response of L. monocytogenes to temperature, oxidative, disinfectant, pH, and osmotic stresses (Oliver et al, 2009;Soni et al, 2011;Tessema et al, 2012;Casey et al, 2014;Tang et al, 2015;Hingston et al, 2017b). Until now, transcriptomic research on L. monocytogenes has been conducted almost exclusively on strains that lack plasmids.…”
mentioning
confidence: 99%
“…To better understand how these strains are able to tolerate the detergents encountered in the food processing environment, the transcriptome responses of persistent and nonpersistent isolates to a sublethal dose of the QAC benzethonium chloride were analyzed (Casey et al, 2014;Fox et al, 2011). A comparison of the transcriptome of the L. monocytogenes persister strain 6179 in the presence and absence of benzethonium chloride showed that genes involved in peptidoglycan biosynthesis, carbohydrate uptake, chemotaxis, and motility were overexpressed (Casey et al, 2014). A comparison of the transcriptome of the L. monocytogenes persister strain 6179 in the presence and absence of benzethonium chloride showed that genes involved in peptidoglycan biosynthesis, carbohydrate uptake, chemotaxis, and motility were overexpressed (Casey et al, 2014).…”
Section: Transcriptional Responses To Environmental Stressesmentioning
confidence: 99%